2021
DOI: 10.1021/jacs.1c08282
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalyzed Stereoselective Polymerization of Vinyl Ethers

Abstract: Isotactic poly(vinyl ether)s (PVEs) have recently been identified as a new class of semicrystalline thermoplastics with a valuable combination of mechanical and interfacial properties. Currently, methods to synthesize isotactic PVEs are limited to strong Lewis acids that require a high catalyst loading and limit the accessible scope of monomer substrates for polymerization. Here, we demonstrate the first Brønsted acid catalyzed stereoselective polymerization of vinyl ethers. A single-component imidodiphosphori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…It should be noted that the current system utilizes the easily available TiCl 2 (OAr) 2 catalyst. It is expected that the utilization of chiral titanium catalysts 26 or chiral organic Brønsted acid catalysts [27][28][29] could lead to better control of the polymerization process.…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the current system utilizes the easily available TiCl 2 (OAr) 2 catalyst. It is expected that the utilization of chiral titanium catalysts 26 or chiral organic Brønsted acid catalysts [27][28][29] could lead to better control of the polymerization process.…”
Section: Papermentioning
confidence: 99%
“…26 Subsequently, this chemistry was expanded to the utilization of chiral organic Brønsted acid catalysts. [27][28][29] One limitation of these systems is the reverse correlation between the stereo-selectivity and monomer loading/concentration, which prevents their potential large-scale applications. Recently, a microreactor-based continuous flow technique has received a lot of attention for polymer synthesis due to its many superior characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new polymerization systems by organocatalysts has been also investigated in the last several years partially because the on–off state of organocatalysts can be controlled by external stimuli such as photoirradiation and electrochemical reactions. 1,1′-Bi-2-naphthol-based bulky and chiral Brønsted acid catalysts achieved the stereoselective polymerization of vinyl ethers to obtain high-molecular-weight isotactic poly­(vinyl ether)­s. Sepunaru et al have prepared multiblock copolymers made of electron-rich monomers and electron-deficient monomers in a single pot using 10-phenylphenothiazine as an organocatalyst by switching between the photo- or electrochemical stimuli . These very interesting results strongly showed that exploring new organocatalytic systems will open a new avenue for polymer synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled cationic polymerization can afford well-defined, narrow dispersity polymers and more recently has offered access to highly isotactic polymers. 18,19 Living anionic polymerization is also well-suited for block copolymer synthesis and control of molecular weight distribution. However, under the conditions tested, we observed instead of vinyl polymerization elimination and substitution reactions of the BN naphthalene ring.…”
Section: Introductionmentioning
confidence: 99%